The Validity and Practicality Test of Textbooks Based on Metacognitive Skills in Blood Circulation System Materials for Grade XI High School - Andi Tenri Ola Rivai; Adnan; Muhammad Junda (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2022)
This research is a research and development which aims to develop a textbook based on metacognitive skills in blood circulation system materials for grade XI high school students that are valid and practical. The development of textbooks based on metacognitive skills refers to the ADDIE development model The stages of analysis, design, development, implementation, and evaluation. The data collection were carried out using several research instruments consisting of: (1) textbook validation instrument to find out textbook validity data assessed by 2 (two) expert validators, (2) teacher and student response instruments to find out the practicality of textbooks. This research was conducted in July-September 2020 at SMA Negeri 9 Makassar. The results of research data analysis obtained: (1) the textbook based on metacognitive skills are valid with a validity value of 4.57, (2) the textbook based on metacognitive skills is practical with the results of the teacher's response being 94.58 with very positive criteria and the results of student responses being 88.85 with very positive criteria. Based on the research that has been finding, it can be concluded that the textbook based on metacognitive skills in blood circulation system materials for grade XI high school students are valid and practical